2013
DOI: 10.1080/0031322x.2013.812349
|View full text |Cite
|
Sign up to set email alerts
|

Ethnicity and social cohesion in the post-Soviet Baltic states

Abstract: This article examines the efforts of post-Soviet Estonia, Latvia and Lithuania to promote social cohesion by addressing the ethnic and linguistic cleavages that are part of the legacy of Soviet rule. In examining the particular situation of each Baltic state and the response to international pressure for integration and social inclusion policy, Muiznieks, Rozenvalds and Birka note the roles of threat-perception, the historic context, the linguistic and citizenship policy, as well as socio-economic inequality, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
30
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 40 publications
(31 citation statements)
references
References 2 publications
0
30
0
1
Order By: Relevance
“…in Latvia conducted by Lebedeva and Tatarko showed that despite the existence of the integration policy formally aimed at preserving Latvian cultural and ethnic identity, integration in this case basically means "the participation of the ethnocultural minority in the life of a dominant society, while there is no direction towards maintaining culture of ethnic minorities; it means that the political term of integration is much closer in meaning to the acculturation expectation of assimilation" (Lebedeva, Tatarko, 2017, p. 319). This reduces the sense of belonging of minorities to their country and enhances the perception of a cultural threat by both minorities and ethnic Latvians (Muiznieks et al, 2013).…”
Section: Interethnic Relations a Study Of Intercultural Relations Bementioning
confidence: 99%
“…in Latvia conducted by Lebedeva and Tatarko showed that despite the existence of the integration policy formally aimed at preserving Latvian cultural and ethnic identity, integration in this case basically means "the participation of the ethnocultural minority in the life of a dominant society, while there is no direction towards maintaining culture of ethnic minorities; it means that the political term of integration is much closer in meaning to the acculturation expectation of assimilation" (Lebedeva, Tatarko, 2017, p. 319). This reduces the sense of belonging of minorities to their country and enhances the perception of a cultural threat by both minorities and ethnic Latvians (Muiznieks et al, 2013).…”
Section: Interethnic Relations a Study Of Intercultural Relations Bementioning
confidence: 99%
“…According to national statistics, the share of ethnic minorities even today constitutes more than half of city's population (CSB, 2017), thus competing with Latvians for better conditions in a free market oriented economy. The studies have confirmed that the members of the Russian-speaking minority in Latvia have adjusted worse to economic restructuring and suffered more from employment losses in different industrial sectors in which they were overrepresented (Aasland, 2002;Lindermann, 2013;Muiznieks et al, 2013). Nevertheless, today slightly more than 75 percent of the inhabitants of Riga live in Soviet-era mass housing areas or neighbourhoods dominated by this distinctive type of housing.…”
Section: Study Contextmentioning
confidence: 93%
“…The assimilationist tendencies of such integration policy affected the sense of belonging in minority groups as well as the perception of cultural threat in both Latvian and Russian communities. In a 2006 study, 34% of Russian-speaking respondents claimed that the Russian language and culture in Latvia is under “somewhat of a threat,” and 35% of the Latvian respondents claimed that the Latvian language and culture in Latvia is under “somewhat of a threat” (Muiznieks, Rozenvalds, & Birka, 2013). This leads to mutual fears and misunderstanding instead of mutual trust and national integration.…”
Section: Current Studymentioning
confidence: 99%